Biophysical characterization of the interaction between M2-1 protein of hRSV and quercetin - Teixeira, Thiago Salem Pançonato [UNESP]; Caruso, Ícaro Putinhon [UNESP]; Lopes, Bruno Rafael Pereira [UNESP]; Regasini, Luis Octávio [UNESP]; Toledo, Karina Alves de [UNESP]; Fossey, Marcelo Andrés [UNESP]; Souza, Fátima Pereira de [UNESP] (Elsevier, 2017)
hRSV is the major causative agent of acute respiratory infections. Among its eleven proteins, M2-1 is a transcription antiterminator, making it an interesting target for antivirals. Quercetin is a flavonol which inhibits some virus infectivity and replication. In the present work, the M2-1 gene was cloned, expressed and the protein was purified. Thermal stability and secondary structure were analyzed by circular dichroism and the interaction with Quercetin was evaluated by fluorescence spectroscopy. Molecular docking experiments were performed to understand this mechanism of interaction. The purified protein is mainly composed of α-helix, with a melting temperature of 328.6 K (≈55 °C). M2-1 titration with Quercetin showed it interacts with two sites, one with a strong constant association K1 (site 1 ≈ 1.5 × 106 M−1) by electrostatic interactions, and another with a weak constant association K2 (site 2 ≈ 1.1 × 105 M−1) by a hydrophobic interaction. Ligand's docking shows it interacts with the N-terminus face in a more polar pocket and, between the domains of oligomerization and RNA and P protein interaction, in a more hydrophobic pocket, as predicted by experimental data. Therefore, we postulated this ligand could be interacting with important domains of the protein, avoiding viral replication and budding.
Keywords: Biophysical analyses; hRSV; M2-1; Molecular docking; Quercetin